EFEK BERBAGAI BIOCHAR DAN PUPUK MAJEMUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) - Januariska, Eri Januariska; Mulyati, Mulyati; A B, Baharuddin (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
This study aimed to determine the effect of biochar, NPK fertilizers and their interaction on the growth and yield of lettuce. This research was carried out in Moncok Village, Ampenan, Mataram City, with a height of 20 m above sea level. The study was conducted from April to June 2017. The study was conducted using a Randomized Block Design (RBD) with factorial patern of 2 factors. The first factor was the type of biochar which consists of B1 (rice husk biochar) and B2 (wood branch biochar). The second factor was the dose of NPK fertilizer consisting of P0 (without NPK fertilizer), P1 (NPK fertilizer 100 kg / ha), P2 (NPK fertilizer 200 kg / ha), and P3 (NPK fertilizer 100 kg / ha). So there were 8 treatment combinations and each treatment was repeated 3 times to obtain 24 experimental plots. The results showed that the interaction between biochar types with NPK fertilizer dose did not affect the plant height, the leaf number, and the weight of biomass per plant and per plot. The type of biochar did not affect the plant height and the number of leaves but affects the weight of the plants per plant, and per plot. The dosage of NPK fertilizer did not affect the plant height and the number of leaves, except at the age of 28 day after planting but had an effect on the weight of plant per plant, and the weight of plant per plot.